Estate Administration in Malaysia: Analysis of The Hire-Purchase Agreement to The Deceased’s Vehicle Repossession - Nasrul, Muhammad Amrullah; Anis A'fifah Zairin Zain; Salim, Wan Noraini Mohd Salim (Alauddin Law Development Journal (ALDEV), 2025)
This paper examines the challenges faced by beneficiaries in managing the estate of a deceased person, specifically in relation to vehicles under hire-purchase agreements. Many beneficiaries are unaware of the procedures outlined in the Malaysian Hire-Purchase Act 1967, which often results in vehicle repossession due to non-payment of installments. In some cases, beneficiaries are also burdened with settling the outstanding loan balance despite the repossession, exacerbating the emotional and financial strain on the deceased’s family. This study focuses on the estate administration process, particularly the transfer of vehicle ownership and explores the legal provisions governing repossession when the hirer passes away during the agreement period. Adopting a qualitative methodology, this research draws upon statutory analysis, case law, academic literature, and seminar papers. The findings reveal that a lack of legal awareness and administrative delays are primary factors contributing to repossession, ultimately causing further financial hardship to the beneficiaries.